Synthesis, Characteristics of Titan Dioxide Nanotube and Photocatalytic Decomposition of Ethanol - Minh, Nguyen Hai; Giang, Vu Ha; Phong, Pham Van; Oanh, Le Thi Hoang; Ha, Hoang Van (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2DO - 10.25073/2588-1140/vnunst.4744, 2018)
In this study, N-doped TiO 2 nanotubes material was synthesized from commercial TiO 2 by hydrothermal synthesis in concentrated sodium solution with high temperature and pressure conditions. The morphology, crystalline phase, composition were characterized by the modern physicochemical techniques such as X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS) and ultraviolet-visible spectrophotometry (UV-Vis). The results showed that TiO 2 nanotubes have the diameter of 10-12 nm and the lengthabout 150 nm witha high specific surface area. The photocatalytic activity of this material was evaluated in terms of photodegradation of ethanol under ultraviolet light, it showed that the photocatalytic activity of nanotubes is higher than nanoparticles and the activity is enhanced when there is nitrogen doping. Keywords Titan dioxide, nanotubes, VOCs, hydrothermal, photocatalysis References 1. K. Hashimoto, H. Irie, A. Fujishima, TiO2 photocatalysis: a historical overview and future prospects, Jpn. J. Appl. Phys., 44(12R), 8269-8285 (2005). 2. Q. Kezhen, C. Bei, Y. Jiaguo, H. Wingkei, A review on TiO‐based Z‐scheme photocatalysts, Chinese Journal of Catalysis, 38(12), 1936-1955 (2017). 3. P. Hoyer, Formation of a titanium dioxide nanotube array, Langmuir, 12(6), 1411-1413 (1996). 4. N. Liu, X. Chen, J. Zhang, J. W. Schwank, A review on TiO2-based nanotubes synthesized via hydrothermal method: Formation mechanism, structure modification, and photocatalytic applications, Catalysis Today, 225, 34-51 (2014). 5. D. V. Bavykin, S. N.Gordeev, A. V. Moskalenko, A. A. Lapkin, F. C. Walsh, Apparent two-dimensional behavior of TiO2 nanotubes revealed by light absorption and luminescence, The Journal of physical chemistry B, 109(18), 8565-8569 (2005). 6. D. V. Bavykin, V. N. Parmon, A. A. Lapkin, and F. C. Walsh, The effect of hydrothermal conditions on the mesoporous structure of TiO2 nanotubes, Journal of Materials Chemistry, 14(22), 3370-3377 (2004). 7. C. L. Wong, Y. N. Tan, and A. R. Mohamed, A review on the formation of titania nanotube photocatalysts by hydrothermal treatment, Journal of environmental management, 92(7), 1669-1680 (2011). 8. A. Elsanousi, E. M. Elssfah, J. Zhang, J. Lin, H. S. Song, and C. Tang, Hydrothermal treatment duration effect on the transformation of titanate nanotubes into nanoribbons, The Journal of Physical Chemistry C, 111(39), 14353-14357 (2007). 9. N. Liu, X. Chen, J. Zhang and J. W. Schwank, A review on TiO2-based nanotubes synthesized via hydrothermal method: Formation mechanism, structure modification, and photocatalytic applications, Catalysis Today, 225, 34-51 (2014). 10. D. V. Bavykin, S. N. Gordeev, A. V. Moskalenko, A. A. Lapkin and F. C. Walsh, Apparent two-dimensional behavior of TiO2 nanotubes revealed by light absorption and luminescence, The Journal of physical chemistry B, 109(18), 8565-8569 (2005). 11. M. H. Razali, M. N. Ahmad-Fauzi, A. R. Mohamed, and S. Sreekantan, Morphological structural and optical properties study of transition metal ions doped TiO2 nanotubes prepared by hydrothermal method, International journal of material, mechanics, and manufacturing, 1(4), 314-318 (2013). 12. J. Y. Kim, C. S. Kim, H. K. Chang, and T. O. Kim, Synthesis and characterization of N-doped TiO2/ZrO2 visible light photocatalysts, Advanced Powder Technology, 22(3), 443-448 (2011). 13. W. Mekprasart, T. Khumtong, J. Rattanarak, W. Techitdheera, and W. Pecharapa, Effect of nitrogen doping on optical and photocatalytic properties of TiO2 thin film prepared by spin coating process, Energy Procedia, 34, 746-750 (2013).